HUSN AL-ZHANN: THE CONCEPT OF POSITIVE THINKING IN ISLAMIC PSYCHOLOGY PERSPECTIVE AND ITS BENEFIT ON MENTAL HEALTH - Ahmad Rusydi (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2012)
This study wants to explain that positive thinking in perspective of Islamic Psychology, and to prove thatpositive thinking and mental health have a significant positive correlation. In Islamic psychology, positivethinking (husn al-zhann) is a qalb behaviour and one of good akhlaq (personality) which motivate tothink positively to the God and others. Doing positive thinking to the God is indicated by tawakkal (trustin God), feeling love and forgiveness. Doing positive thinking to the others is indicated by absence oftajassus, tahassus, hatred, and hasad. The correlational anlysis found that positive thinking and mentalhealth have a significant positive correlation (r=0,364/ sig=0,001). The regression anlysis found thatpositive thinking to the God is more influence on mental health (t= 3,409/ sig=0,001) than positivethinking to the others (t= -0,271/ sig=0,787).